(untitled) (Bangladesh Journal of Plant Taxonomy, 2016)
The paper presents pollen micromorphology by scanning electron microscopy of seven Anabasis L. species namely, A. haussknechtii Bge., A. aphylla L., A. calcarea (Charif & Allen) Bokhari & Wendelbo, A. eugeniae Iljin, A. eriopoda (Shrernk) Volkens, A. annua Bge. and A. setifera Moq. from Iran. Pollen grains in all studied species are peripolyporate, spherical and are of two basic types based on pores diameter inner of holes. The study showed that the sculpturing of exine provides valuable characters in species delimitation, sometimes even for closely related ones. An artificial key based on pollen characters for seven species is provided. Bangladesh J. Plant Taxon. 23(2): 247-253, 2016 (December)